Surgery alters parameters of vitamin D status and other laboratory results. Issue 3 (March 2017) - Binkley, N.; Coursin, D.; Krueger, D.; Iglar, P.; Heiner, J.; Illgen, R.; Squire, M.; Lappe, J.; Watson, P.; Hogan, K.
Abstract Summary Fracture liaison services often perform laboratory testing, but these results may be altered by surgery. In 40 hip arthroplasty patients, many laboratory parameters of bone health relevance were reduced by 8–22% on the first post-operative day. Laboratory results obtained in the immediate post-surgery interval do not reliably ascertain baseline status. Introduction As secondary causes of osteoporosis are common, fracture liaison services often perform laboratory testing in the immediate post-fracture interval. We hypothesized that laboratory results obtained shortly after surgery may not accurately ascertain baseline status. If true, such alterations might confound subsequent fracture prevention efforts. Methods Patients undergoing elective total hip arthroplasty were studied as a surrogate for hip fracture patients. Blood and urine were obtained 2 weeks before surgery, before anesthetic induction, on post-operative day one, and 6 weeks after surgery. Serum total and free 25-hydroxyvitamin D (25(OH)D), vitamin D-binding protein (DBP), calcium, creatinine, albumin (Alb), alkaline phosphatase (ALP), plasma hemoglobin (Hgb) and urinary DBP/creatinine ratio (UDBP/Cr) were measured. Results Forty volunteers (28 women; 12 men) with mean age of 65.7 [8.7] years were studied. Laboratory results were stable from 2 weeks before to the day of surgery. On the first day after surgery, total 25(OH)D, DBP, calcium, creatinine, ALP, and Alb declined 8–22% (p < 0.0001); free 25(OH)D and Hgb declined by 8 and 15% (p < 0.01), respectively; and UDBP/Cr increased 32% (p < 0.01). Using a 25(OH)D <30 ng/mL threshold, vitamin D inadequacy prevalence increased from 38% before surgery to 68% the day after (p < 0.001). All laboratory values returned to baseline at 6 weeks after surgery. Conclusions Laboratory values are reduced immediately following elective total hip arthroplasty. Testing at that time does not accurately ascertain baseline status and may lead to elevated estimates of vitamin D inadequacy, incorrect interventions, and misallocation of healthcare resources.